The role of financial innovation in achieving sustainable finance to support sustainable development at the global level during the period (2010-2021) - بلعيد , محمد; علية , عبد الباسط عبد الصمد (Finance and Business Economies Review, 2023)
This study aims to clarify the role of financial innovation in achieving sustainable finance, and to investigate the impact of innovative financial products for sustainable finance represented by the size of the annual issuance of sustainable bonds and the net investment of sustainable investment funds on sustainable development at the global level during the period (2010-2021), using (ARDL) models. The study found a positive impact of the size of the annual issuance of sustainable bonds on sustainable development at the global level in the short term, the sustainable bond market has witnessing remarkable development both in terms of the size of the issuance and in terms of the diversity of sustainable bond types available.